Kuat Tekan Beton Dengan Menggunakan Agregat Halus Gunung Sugih, Agregat Kasar Sumber Batu Berkah Dan Abu Batu Sumber Batu Berkah Tarahan - Girinandi, Irwan; Riyanto, Heri (Jurnal Profesi Insinyur Universitas Lampung, 2020)
The development of the construction industry and transportation continue to show a significant increase with the increasing number of people and also the needs of humanity. Lampung province developed as well as an increase in charges. Part of construction that encounter development is concrete. High compressive strength of concrete with an affordable price start to be research to mixing modifications with the use of additive. One of modifications is mixing with stone ash as additive. This research explains about concrete compressive strength which mixed by good quality aggregate and stone ash in lampung area. Fine aggregate that used was natural aggregate from Gunung Sugih while coarse aggregate was crushed stones from Sumber Batu Berkah quarry. This research was done at Laboratory facilty of Bandar Lampung University. The use of stone ash was done in partial substitusion for 10%, 20%, 30%, 40% and 50% of coarse aggregate start from the biggest gradation. From the result of this research, the highest compressive strength was discovered in concrete with 30% use of stone ash which was 451,837 kg/m2. The maximum compressive strength was increase about 18,76% in comparation of 10 % use of stone ash and decreased about 6,17 % in the use of 50 % ston ash. The density of every level of stone ash use follow the same record of compressive strength. The density weight in 30% variants use of stone ash which is superior than 10 % and 50 % variants.